(untitled) (Acta Scientiarum. Biological Sciences, 2012)
This study described the karyotype of Geophagus cf. proximus. Specimens were collected in Ãgua Preta Lake, Parque Ambiental de Belém, Pará State, Brazil. The karyotype were 2n = 48 chromosomes (FN = 60: 12M/SM+36ST/A) and no sexual chromosome differentiation. C-banding showed centromeric staining in all chromosomes. The first chromosome pair, besides centromeric coloration, presented a totally heterochromatic long arm. The nucleolus organizer regions (NORs) were studied by means of AgNO3. NORs were located at the short arm of the second chromosome pair.